2018
DOI: 10.1002/acr.23284
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Inflammation in Rheumatoid Arthritis: Does Patient Global Assessment Blur the Target? A Practice‐Based Call for a Paradigm Change

Abstract: Objective In current management paradigms of rheumatoid arthritis (RA), patient global assessment (PGA) is crucial to decide whether a patient has attained remission (target) or needs reinforced therapy. We investigated whether the clinical and psychological determinants of PGA are appropriate to support this important role. Methods This was a cross‐sectional, single‐center study including consecutive ambulatory RA patients. Data collection comprised swollen 28‐joint count (SJC28), tender 28‐joint count (TJC28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 45 publications
6
109
0
2
Order By: Relevance
“…Debate is ongoing about the future of the PGA‐VAS in RA remission criteria. Proposals include removing the PGA‐VAS from remission criteria , using model disease states to orient the patients to a standard of comparison similar to that used by providers , using patient‐reported outcomes that capture the patient perspective of remission to either replace or augment the PGA‐VAS , or to raise the PGA‐VAS remission target to a more forgiving level . In light of these controversies, our data, which question the validity of model disease state ratings and difficulties in VAS completion for those of limited health literacy and with possible mental health issues, are particularly valuable and add urgency to the growing sense that the PGA‐VAS needs to be re‐examined as a criterion of remission .…”
Section: Discussionmentioning
confidence: 99%
“…Debate is ongoing about the future of the PGA‐VAS in RA remission criteria. Proposals include removing the PGA‐VAS from remission criteria , using model disease states to orient the patients to a standard of comparison similar to that used by providers , using patient‐reported outcomes that capture the patient perspective of remission to either replace or augment the PGA‐VAS , or to raise the PGA‐VAS remission target to a more forgiving level . In light of these controversies, our data, which question the validity of model disease state ratings and difficulties in VAS completion for those of limited health literacy and with possible mental health issues, are particularly valuable and add urgency to the growing sense that the PGA‐VAS needs to be re‐examined as a criterion of remission .…”
Section: Discussionmentioning
confidence: 99%
“…First, we demonstrated that there were almost twice as many patients in PGA‐near‐remission status as those in “full” remission in an international cohort (Ferreira, Carvalho, et al, ), and up to 37% of all patients in some settings (Ferreira, Duarte, et al, ). Among these PGA‐near‐remission patients, about one‐third scored a PGA >4/10 (Ferreira, Carvalho, et al, ).…”
Section: Inclusion Of Proms May Challenge the Treatment Target(s)mentioning
confidence: 74%
“…Finally, we showed that PGA from patients in near‐remission is not associated with disease activity but rather with fatigue, pain, anxiety, depression, physical well‐being and functional limitations (Ferreira et al, ; Ferreira, Duarte, et al, , Ferreira, Carvalho, et al, ).…”
Section: Inclusion Of Proms May Challenge the Treatment Target(s)mentioning
confidence: 93%
“…Rheumatol. 13, 573-574 (2017)) 1 referring to our paper on the role of patient global assessment (PGA) in the definition of remission in rheumatoid arthritis (RA) 2 . However, we cannot agree with their interpretation that by suggesting to remove the PGA from the ACR/EULAR remission definition we are "calling for a paradigm change that limits the responsibility of the rheumatologist to prescribing immunosuppressive therapy, " or that our proposal is "taking away the incentive to improve RA care by removing the patient's perspective from the remission criteria. "…”
mentioning
confidence: 99%
“…This consideration suggests that clinical practice should be guided by two separate remission targets: inflammation (3v-remission) and disease impact. " 2 In summary, we do not propose to "limit the responsibility of the rheumatologist to prescribing immunosuppressive therapy" 1 , but rather we want to highlight the rheumatologist´s and multidisciplinary team's responsibility to assess and manage disease impact. The appropriateness of these proposals will be further scrutinized by clarifying whether high PGA in patients otherwise in remission is associated with subclinical inflammation and whether full remission is a better predictor than 3v-remission (without PGA) of a long-term good radiological outcome 5 .…”
mentioning
confidence: 99%